Seed Priming Based on Iodine and Selenium Influences the Nutraceutical Compounds in Tomato (Solanum lycopersicum L.) Crop - Fernando Mejía-Ramírez; Adalberto Benavides-Mendoza; Susana González-Morales; Antonio Juárez-Maldonado; Francisco Marcelo Lara-Viveros; América Berenice Morales-Díaz; Álvaro Morelos-Moreno (MDPI AG, 2023)
The use of trace elements in agriculture as a complement to crop fertilization programs is a practice that is gaining importance and relevance worldwide. Iodine and selenium perform essential functions in human health, related to the proper functioning of the thyroid gland, acting as antioxidants and antiproliferatives, and their limited intake through food consumption can cause malnutrition, reflected in the abnormal development and growth of humans. This research aimed to evaluate the nutraceutical quality of tomato (Solanum lycopersicum L.) in response to seed priming based on KIO3 (0, 100, 150, 200, 250 mg L−1) and Na2SeO3 (0, 0.5, 1, 2, 3 mg L−1), performed by interaction from a 52-factorial design and by independent factors in a 24-h imbibition time. The tomato crop was established under greenhouse conditions in 10-L polyethylene containers containing peat moss and perlite 1:1 (v/v). Regarding non-enzymatic antioxidant compounds, lycopene, β-carotene and flavonoid contents in tomato fruits significantly increased with KIO3 and Na2SeO3 treatments; however, vitamin C content was negatively affected. KIO3 increased the phenol and chlorophyll-a contents of leaves. In relation to enzymatic activity, KIO3 positively influenced GSH content and PAL activity in tomato fruits. KIO3 also positively influenced GSH content in leaves while negatively affecting PAL and APX activities. Na2SeO3 favored GSH content and GPX activity in tomato fruits and leaves. Na2SeO3 negatively affected the antioxidant capacity of hydrophilic compounds by ABTS in fruits and leaves and favored hydrophilic compounds by DPPH in leaves. Seed imbibition based on KIO3 and Na2SeO3 is a method that is implemented in the tomato crop and presents interesting aspects that favor the nutraceutical quality of tomato fruits, which may contribute to increasing the intake of these minerals in humans through tomato consumption.